Pembiayaan Perumahan Syariah Berbasis Akad Murabahah bil Wakalah dalam Perspektif Fatwa DSN No.04/DSN-MUI/IV/2000 - Rahmadini, Tasyana; Trigiyatno, Ali; Yaqin, 'Alamul (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
The main problem of this research is how Islamic housing financing based on murabahah bil wakalah contract at PT Bank BTN Syariah Pekalongan branch office and sharia housing financing based on Murabahah bil Wakalah contract at PT. Bank BTN Syariah Pekalongan Branch Office in Perspective of Fatwa DSN No.04/DSN- MUI/IV/2000. The purpose of this study was to determine Islamic housing financing based on the Murabahah bil wakalah contract at PT Bank BTN Syariah Pekalongan Branch Office and Islamic housing financing based on the Murabahah bil Wakalah contract at PT Bank BTN Syariah Pekalongan Branch Office in the Perspective of Fatwa DSN No.04/DSN- MUI/IV/2000. This type of research is a field research (field-research) with a qualitative approach. Sources of data in the form of primary and secondary data, primary data obtained by interview and observation techniques while secondary data obtained by documentation. The subject of this research is PT. Bank BTN Syarih Pekalongan Branch Office and Customers. while the object is the settlement in accordance with the DSN Fatwa No.04/DSN-MUI/IV/2000 in the Murabahah bil Wakalah contract. And data analysis using descriptive qualitative. This research can be concluded that the implementation of the Murabahah bil Wakalah contract fulfills the financing requirements and is not in accordance with the DSN Fatwa No.04/DSN-MUI/IV/2000 because in the practice of the Murabahah bil Wakalah contract, this financing performs the contract before the goods are fully owned by the bank.